Order Integrals - de Jeu, Marcel; Jiang, Xingni (arXiv.org, 2021)
We define an integral of real-valued functions with respect to a measure that takes its values in the extended positive cone of a partially ordered vector space \(E\). The monotone convergence theorem, Fatou's lemma, and the dominated convergence theorem are established; the analogues of the classical \({\mathcal L}^1\)- and \({\mathrm L}^1\)-spaces are investigated. The results extend earlier work by Wright and specialise to those for the Lebesgue integral when \(E\) equals the real numbers. The hypothesis on \(E\) that is needed for the definition of the integral and for the monotone convergence theorem to hold (\(σ\)-monotone completeness) is a rather mild one. It is satisfied, for example, by the space of regular operators between a directed partially ordered vector space and a \(σ\)-monotone complete partially ordered vector space, and by every JBW-algebra. Fatou's lemma and the dominated convergence theorem hold for every \(σ\)-Dedekind complete space. When \(E\) consists of the regular operators on a Banach lattice with an order continuous norm, or when it consists of the self-adjoint elements of a strongly closed complex linear subspace of the bounded operators on a complex Hilbert space, then the finite measures as in the current paper are precisely the strongly \(σ\)-additive positive operator-valued measures. When \(E\) is a partially ordered Banach space with a closed positive cone, then every positive vector measure is a measure in our sense, but not conversely. Even when a measure falls into both categories, the domain of the integral as defined in this paper can properly contain that of any reasonably defined integral with respect to the vector measure using Banach space methods.